THE INFLUENCE OF BUSINESS CAPITAL FINANCING ON THE IMPROVEMENT OF CUSTOMER BUSINESSES AT KSPPS BMT NU EAST JAVA ON THE MADURESE COMMUNITY - Nashar; Addainuri, Muhammad Isbad (Journal on Islamic Economics, Finance & Banking [Z-CONOMICS], 2025)
Sharia Financing Savings and Loan Cooperative BMT NU East Java is a bank that operates according to sharia principles. One of the most important differentiators that a sharia bank must have is a strategy to retain customers who take out loans through excellent service, assistance and education, and emotional relationships. Based on observations, there is a unique aspect to the business capital financing of the Sharia BMT NU East Java Savings and Loan Cooperative. The purpose of this study is to determine and analyze the effect of business capital financing on the growth of customer businesses at KSPP. Sharia BMT NU East Java, as well as to obtain empirical data on whether or not business capital financing has an effect on the growth of customer businesses at KSPP. Syariah BMT NU East Java. This research uses a quantitative approach with simple linear regression analysis techniques using the SPSS 20 analysis tool. Meanwhile, hypothesis testing uses t-test calculations. The population in this study consisted of 35 customers. The sample used a saturated sample or census. The data collection technique used a questionnaire (survey). The results show that: first, with the t-test, the business capital financing variable shows 0.000, which is smaller than a (0.000 < 0.05). The t-count value is > t-table (7.909 > 1.68957). This means that business capital financing has a significant effect on business growth. Second, the R Square value obtained is 0.655 or 65.5%. This means that 65.5% of the regression model in this study explains the dependent variable (Business Growth), while the remaining 34.5% is influenced by variables not taken into account in the study.